Raise Your Voices and Kill Your Animals : Islamic Discourses on the Idd el-Hajj and Sacrifices in Tanga (Tanzania). - Van de Bruinhorst, G. C. (ISIM dissertations., 2007)
"Raise Your Voices and Kill Your Animals" is an anthropological study in which G.C. van de Bruinhorst explores the relationship between Islamic texts and ritual behaviour as illustrated in the annual Sacrificial Feast in Tanzania.